Design of transformerless inverter using H-Bridge Mosfet as a switching device - Muhammad Rafiq, Muhammad Amin (2013)
This thesis presents the performance of efficiency of and low the cost of transformerless inverter which is convert high voltage DC into pure sine wave 220Vac, 50Hz power. A microcontroller is used to generate pulse width modulation technique for a greater efficiency. The four MOSFETs switching components with configuration of 'H' shape (H-bridge) were chosen to handling a maximum of 500 Watts.